Assessment of genetic variability, heritability and genetic advance in Indian mustard (Brassica juncea L.) (Journal of Oilseed Brassica, 2026)
Forty-five genotypes of Indian mustard (Brassica juncea L.) were evaluated during rabi 2021-22 under four environments created through different dates of sowing (timely sown 20 Oct. and late sown 20 Nov.) and row to row spacing (normal 30 × 10 cm and reduced 20 × 10 cm) i.e. timely sown, normal spacing (E1), timely sown, reduced spacing (E2), late sown, normal spacing (E3), late sown, reduced spacing (E4). Pooled analysis of variance revealed significant differences among genotypes, environments and G × E for all the traits. Therefore, analysis of variance carried out separately for each environment which indicated significant difference among all the genotypes for 14 traits under all environments. The variability studies showed high phenotypic (PCV) and genotypic (GCV) coefficient of variation for number of siliquae per plant, seed yield per plant and first branch initiation height in all the environments (except in E4 for first branch initiation height), whereas, moderate GCV and PCV were recorded for plant height, primary branches per plant, 1000-seed weight, number of seeds per siliqua and harvest index in all the environments. Estimate of high heritability along with high genetic advance as per cent of mean were observed for number of siliquae per plant, seed yield per plant, first branch initiation height, plant height, number of primary branches per plant, 1000-seed weight, number of seeds per siliqua and harvest index in all the environments. Likewise, siliqua length had high heritability along with moderate genetic advance as per cent of mean considered for all the four environments. Thus, these characters might be under the control of additive gene action and direct selection based on these traits could be advantageous.